2020
DOI: 10.1177/0363546519894323
|View full text |Cite
|
Sign up to set email alerts
|

PROMIS Versus Legacy Patient-Reported Outcome Measures in Patients Undergoing Surgical Treatment for Symptomatic Acetabular Dysplasia

Abstract: Background: No previous study has investigated how the Patient-Reported Outcomes Measurement Information System (PROMIS) performs compared with legacy patient-reported outcome measures in patients with symptomatic acetabular dysplasia treated with periacetabular osteotomy (PAO). Purpose: To (1) measure the strength of correlation between the PROMIS and legacy outcome measures and (2) assess floor and ceiling effects of the PROMIS and legacy outcome measures in patients treated with PAO for symptomatic acetabul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…The moderately strong correlation at 6 months after surgery reported by Nwachukwu et al 10 is slightly different, given that prior studies have shown a strong correlation of PROMIS PF to the iHOT-12, including the current authors' prior research. [7][8][9] In my opinion, all these studies confirm what multiple authors have concluded: PROMIS PF, which is a general measure of physical function, correlates to legacy hip measures. Nwachukwu et al chose to compare the relative efficiency (RE) of one measure with that of another.…”
Section: See Related Article On Page 2992supporting
confidence: 84%
See 1 more Smart Citation
“…The moderately strong correlation at 6 months after surgery reported by Nwachukwu et al 10 is slightly different, given that prior studies have shown a strong correlation of PROMIS PF to the iHOT-12, including the current authors' prior research. [7][8][9] In my opinion, all these studies confirm what multiple authors have concluded: PROMIS PF, which is a general measure of physical function, correlates to legacy hip measures. Nwachukwu et al chose to compare the relative efficiency (RE) of one measure with that of another.…”
Section: See Related Article On Page 2992supporting
confidence: 84%
“…Multiple authors have shown moderately strong to strong correlations of PROMIS measures to legacy hip scores. [7][8][9] PROMIS, specifically PROMIS Physical Function (PF), has previously been shown to strongly correlate to legacy measures. 7,8 With correlation, we must ask ourselves, Is the correlation meaningful?…”
Section: See Related Article On Page 2992mentioning
confidence: 99%
“…Also, the use of several PROs designed for active patients with nonarthritic hips limits a potential ceiling effect. 27,55 The current study aimed for a narrow patient population in the hip preservation field; nonetheless, an adequate sample size based on a priori power analysis was achieved for the study and control groups. Additionally, to surpass statistical significance and demonstrate clinical significance, the fraction of patients who achieved the MCID for the mHHS, NAHS, HOS-SSS, and VAS was calculated.…”
Section: Discussionmentioning
confidence: 99%
“…There has been little overall study on psychometric properties of the PROMIS score in relation to hip pathology. In a study of patients who underwent periacetabular osteotomy for symptomatic hip dysplasia, PROMIS showed no floor or ceiling effects both pre‐ and postoperatively . When studied in patients who underwent THA for symptomatic hip osteoarthritis, the PROMIS depression domain showed floor effects up to 20% preoperatively and 30% to 45% postoperatively .…”
Section: Patient‐reported Outcomes Measurement Information Systemmentioning
confidence: 94%
“…The HOOS is one of the more common patient‐reported measures of hip function and postoperative outcomes. It has been used extensively in THA clinical studies , hip dysplasia surgery , hip arthroscopy , and even in development of pain management protocols after hip surgery . The HOOS‐JR has only existed since 2016 and is intended mainly for THA, but it has been used in recent trials related to THA outcomes .…”
Section: Hip Disability and Osteoarthritis Outcome Scorementioning
confidence: 99%